2007
DOI: 10.3758/bf03194082
|View full text |Cite
|
Sign up to set email alerts
|

Displaywide visual features associated with a search display’s appearance can mediate attentional capture

Abstract: Whether or not the capture of visual attention is driven solely by the salience of an attention-capturing stimulus or mediated by top-down control has been a point of contention since Folk, Remington, and Johnston (1992) introduced their contingent involuntary orienting hypothesis, which states that the capture of attention by a salient stimulus depends on its relevance to a feature distinguishing the target from nontargets. Gibson and Kelsey (1998) extended Folk et al.'s (1992) hypothesis by demonstrating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 128 publications
(153 reference statements)
5
103
3
Order By: Relevance
“…Our experimental design did not provide a definitive explanation for the generalized performance cost at +100 ms, but a likely reason is attentional capture by the central cue (Ansorge, Horstmann & Carbone, 2005;Belopolsky, Schreij & Theeuwes, 2010;Burnham, 2007;Eimer & Kiss, 2008;Eimer, Kiss, Press & Sauter, 2009;Folk, Remington, & Johnston, 1992;Gibson & Kelsey, 1998). We found that informative, Cuing benefited performance at a cue-target SOA of −1,000 ms, but impaired performance at a cue-target SOA of +100 ms. c Flanker benefits and costs at different target-flanker SOAs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our experimental design did not provide a definitive explanation for the generalized performance cost at +100 ms, but a likely reason is attentional capture by the central cue (Ansorge, Horstmann & Carbone, 2005;Belopolsky, Schreij & Theeuwes, 2010;Burnham, 2007;Eimer & Kiss, 2008;Eimer, Kiss, Press & Sauter, 2009;Folk, Remington, & Johnston, 1992;Gibson & Kelsey, 1998). We found that informative, Cuing benefited performance at a cue-target SOA of −1,000 ms, but impaired performance at a cue-target SOA of +100 ms. c Flanker benefits and costs at different target-flanker SOAs.…”
Section: Discussionmentioning
confidence: 52%
“…Contingent attentional capture occurs when the task-irrelevant stimulus contains task-defining features, as was the case with our flankers. It has been found that contingent attentional capture can easily override goal-directed attention (Ansorge et al, 2005;Belopolsky et al, 2010;Burnham, 2007;Eimer & Kiss, 2008;Eimer et al, 2009;Folk et al, 1992;Gibson & Kelsey, 1998). We suggest that flankers preceding the target capture attention, and this involuntary process is unchanged by endogenous cuing.…”
Section: Discussionmentioning
confidence: 85%
“…Much research has revealed an interaction between topdown settings and bottom-up signals on the control of attention (e.g., Anderson & Folk, 2010;Ansorge & Heumann, 2003;Folk & Remington, 1998Folk et al, 1992;Folk et al, 1994;Gibson & Kelsey, 1998; for reviews, see Burnham, 2007;Theeuwes, 2010). But according to the attentional disengagement account, all salient stimuli capture attention in a stimulus-driven manner.…”
Section: Response Time Distributionmentioning
confidence: 99%
“…The contingent capture hypothesis, on the contrary-that top-down control determines initial attentional selectionalso has accumulated support (Al-Aidroos, Harrison, & Pratt, 2010;Atchley, Kramer, & Hillstrom, 2000;Bacon & Egeth, 1994;Burnham, 2007;Chen & Mordkoff, 2007;Folk, Leber, & Egeth, 2002;Folk & Remington, 1998, 1999Folk et al, 1992;Folk et al, 1994;Gibson & Kelsey, 1998;Leber & Egeth, 2006;Liao & Yeh, 2011). In a series of studies, Folk and colleagues showed that in a search for a red letter among white letters, only a task-irrelevant red distractor (but not an onset distractor) captured attention (e.g., Folk & Remington, 1998, 1999Folk et al, 1992;Folk et al, 1994).…”
mentioning
confidence: 99%